FENOMENA HIJAB FESYEN PADA MAHASISWI UNIVERSITAS UDAYANA - Cahyaning Putri, Anggraeni Nur; Zuryani, Nazrina; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT This study aims to analyze also explain the reasons and motivations of Muslim female students related to fashion trends in using hijab within the scope of Udayana University. The approach being used in this study utilises descriptive explorative and uses David Chaney's lifestyle theory analysis. The field research in Udayana University found that wearing hijab creation is increasing by those female students. So, the assumption that hijab makes girls are not beautiful, seems old-fashioned and inflexible, can fade along with the presence of a hijab fashion. In addition to that, several models of hijab such as conventional models, pashmina, paris, rawis, syar'i, and so on, are models and styles that are highly choosen by Udayana University students because of the prices and models that are easily matched with their needs. Keywords; Fashion, Lifestyle, Hijab, College Students